PENGEMBANGAN MODUL BIOTEKNOLOGI BERORIENTASI KEWIRAUSAHAAN GUNA MENINGKATKAN MINAT ENTERPREUNER SISWA SMA/MA - Deden Ibnu Aqil; Adeng Hudaya; Nur Amega Setiawati (EDUSAINS, 2021)
THE DEVELOPMENT OF AN ENTREPRENEUR-ORIENTED BIOTECHNOLOGY MODULE TO IMPROVE ENTREPRENEUR INTEREST IN SMA / MA STUDENTSAbstractThis research aimed to determine the application of learning models in increasing student interest in entrepreneurship. This biotechnology lesson was taken because this lesson contains an understanding of the use of biological materials in products that students can develop into entrepreneurial products. This research is a research and development (R&D) arranged systematically consisting of defining, designing, developing, and disseminating. The results of this study from the subject expert analysis, namely the feasibility of the content, shows a percentage of 81.25% is included in the very feasible category. The presentation feasibility percentage found of 80.00% is still a very feasible category. Regarding language feasibility, it got a percentage of 83.33%, which was still in the very feasible category, and for contextual assessment, it got a percentage of 80.55%. From media experts of the 75% eligible category. It was in the feasible category criteria. In terms of module design, 61.11% is a feasible category and module content design is 91.25% very feasible. Based on the results of tests carried out by students, the aspect of the module display was 84.58%, of the content presented was 83.46%, entrepreneurial aspects were 86.32%. Modules fall into the category of proper evaluation and are so worthy that they only need to be slightly revised. AbstrakKegiatan penelitian ini bertujuan mengetahui penerapan model pembelajaran dalam meningkatkan minat enterpreuner siswa. Pelajaran bioteknologi ini diambil karena pelajaran ini mengandung pemahaman tentang pemanfaatan bahan hayati  menjadi produk yang bisa dikembangkan siswa menjadi produk kewirausahaan. Penelitian ini merupakan penelitian dan pengembangan (R & D) yang disusun secara sistematis terdiri dari define/penetapan, design/perancangan, develop /pengembangan, dan disseminate/penyebaran. Hasil penelitian ini dari analisis ahli materi yaitu kelayakan isi menunjukan presentase 81,25% termasuk dalam kategori sangat layak, kemudian dalam kelayakan Penyajian didapat presentase sebasar 80,00 % masih kategori sangat layak. Dalam hal kelayakan Penyajian didapat presentase sebesar 80,00 %, kemudian dalam hal kelayakan Bahasa mendapat presentase sebesar 83,33% masih dalam kategori sangat layak dan untuk penilaian kontekstual mendapatkan presentase sebesar 80,55%. dari ahli media dari ukuran 75 % kategori layak. Dari sisi kriteria masuk dalam kategori layak, dari sisi desain modul 61,11 % kategori layak dan Desain isi modul 91,25 % sangat layak. Berdasarkan hasil pengujian yang dilakukan oleh siswa dari aspek tampilan modul sebesar 84,58% dari penyajian materi sebesar 83,46%, aspek kewirausahaan 86,32 %. Modul termasuk dalam kategori penilian layak dan sangat layak sehingga hanya perlu sedikit direvisi.